2021
DOI: 10.1590/s1678-9946202163027
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to chlorhexidine and mupirocin among methicillin-resistant Staphylococcus aureus clinical isolates from a teaching hospital

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The high resistance to fusidic acid (46.2%) exceeds by far that observed among MRSA globally (2.6%) (Hajikhani et al 2021). The resistance rate to mupirocin (15.4%) was higher than the 3.1% revealed in a previous multicenter surveillance study (Kresken et al 2004); this is of crucial importance since resistance to mupirocin could potentially diminish the e cacy of MRSA decolonizing strategies (Bes et al 2021). For both antimicrobials (fusidic acid and mupirocin) further studies are needed to elucidate the genetic background of the increased resistance (whether it is due to mutation(s) and/or acquired resistance genes).…”
Section: Discussionmentioning
confidence: 75%
“…The high resistance to fusidic acid (46.2%) exceeds by far that observed among MRSA globally (2.6%) (Hajikhani et al 2021). The resistance rate to mupirocin (15.4%) was higher than the 3.1% revealed in a previous multicenter surveillance study (Kresken et al 2004); this is of crucial importance since resistance to mupirocin could potentially diminish the e cacy of MRSA decolonizing strategies (Bes et al 2021). For both antimicrobials (fusidic acid and mupirocin) further studies are needed to elucidate the genetic background of the increased resistance (whether it is due to mutation(s) and/or acquired resistance genes).…”
Section: Discussionmentioning
confidence: 75%
“…It should be emphasized that this conclusion is limited to bacterial isolates exhibiting a chlorhexidine tolerance equal to or less than 32 µg mL −1 ; however, recent studies investigating the in situ development of chlorhexidine resistance in bacterial isolates obtained from HCAI-patient wounds and patient-care fomites have provided evidence supporting the extent of healthcare-associated chlorhexidine resistance to be ≤8 µg mL −1 . [52] While the majority of antimicrobial technologies used in infrastructure materials work by leaching antimicrobials from the surface, [53] the chlorhexidine used in the technology reported here is bonded to the surface, and leaching of the chlorhexidine was not observed. This lack of leaching from the surface could potentially enhance the duration of antimicrobial efficacy against bacteria, especially resistant strains, which often rely on efflux pumps to remove antimicrobials.…”
Section: Discussionmentioning
confidence: 98%
“…A recent review by Dadashi et al (2020) has shown that the global prevalence of mupirocin resistance may be as little as 1.0% in some regions (for studies performed in certain areas of Australia, India, France and Iran, for example) to more than 50% (studies from the United States of America, Egypt and other areas from India). Recent studies with Brazilian Staphylococcus strains from hospitals have reported mupirocin resistance frequencies ranging from 2% (Bes et al 2021) to 33% (Chamon et al 2017). In Staphylococcus isolated from domestic animals from Brazil, these frequencies were considerably lower, from 0.8% in strains isolated from dogs (Rossi et al 2018) to 1% in strains isolated from cats (Rossi et al 2017).…”
Section: Discussionmentioning
confidence: 99%